Minimization of common-mode conducted noise in PWM inverter-fed AC motor drive systems using optimized passive EMI filter - Jettanasen, C.; Ngaopitakkul, A. (My University, 2010)
Conducted electromagnetic interference (EMI) generated by PWM inverter-fed induction motor drive systems, which are currently widely used in many industrial and/or avionic applications, causes severe parasitic current problems, especially at high frequencies (HF). These restrict power electronic drive's evolution. In order to reduce or minimize these problems, several techniques can be applied. In this paper, insertion of an optimized passive EMI filter is proposed. This filter is optimized by taking into account real impedances of each part of a considered AC motor drive system contrarily to commercial EMI filters designed by considering internal impedance of disturbance source and load, equal to 50Ω. Employing the latter EMI filter would make EMI minimization less effective. The proposed EMI filter optimization is mainly dedicated to minimize common mode (CM) currents due to its most dominant effects in this kind of system. The efficiency of the proposed optimization method using two-port network approach is deduced by comparing the minimized CM current spectra to an applied normative level (ex. DO-160D in aeronautics).
Keywords: AC motor drive; Common mode conducted noise; Optimization; Passive EMI filter